Direct simulations of helical Hall-MHD turbulence and dynamo action - Mininni, Pablo Daniel (2005)
Direct numerical simulations of turbulent Hall dynamos are presented. The evolution of an initially weak and small-scale magnetic field in a system maintained in a stationary turbulent regime by a stirring force at a macroscopic scale is studied to explore the conditions for exponential growth of the magnetic energy. Scaling of the dynamo efficiency with Reynolds numbers is studied, and the resulting total energy spectra are found to be compatible with a Kolmogorov-type law. A faster growth of large-scale magnetic fields is observed at intermediate intensities of the Hall effect.